2010
DOI: 10.1186/1465-9921-11-28
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of IL-6 in the allergic asthmatic airway is independent of inflammation but associates with loss of central airway function

Abstract: BackgroundAsthma is a chronic inflammatory disease of the airway that is characterized by a Th2-type of immune response with increasing evidence for involvement of Th17 cells. The role of IL-6 in promoting effector T cell subsets suggest that IL-6 may play a functional role in asthma. Classically IL-6 has been viewed as an inflammatory marker, along with TNFα and IL-1β, rather than as regulatory cytokine.ObjectiveTo investigate the potential relationship between IL-6 and other proinflammatory cytokines, Th2/Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
124
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(138 citation statements)
references
References 46 publications
6
124
1
2
Order By: Relevance
“…Both IL-6 and IL-13 levels are usually elevated in asthma patients and are presumed to be closely correlated [19]; we found that IL-6 levels were similar to IL-13 levels, supporting this idea. IL-13 and IL-6 levels after treatment with 500 mg/kg O. humifusa were notably lower than their levels after dexamethasone treatment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Both IL-6 and IL-13 levels are usually elevated in asthma patients and are presumed to be closely correlated [19]; we found that IL-6 levels were similar to IL-13 levels, supporting this idea. IL-13 and IL-6 levels after treatment with 500 mg/kg O. humifusa were notably lower than their levels after dexamethasone treatment.…”
Section: Discussionsupporting
confidence: 82%
“…Mast cells respond to inflammatory inducers in the early phase and release TNF-α to bring on typical asthma characteristics, such as contracting smooth muscles [14], attracting neutrophils and eosinophils [17], and activating T cells [18]. IL-6 is an important factor that regulates asthma induction via CD4+ cell modulation [19]. …”
Section: Introductionmentioning
confidence: 99%
“…IL-6 is linked to allergic responses involving asthma [21], while IL-8 is associated with chronic obstructive pulmonary disease (COPD) [22]. IL-6 stimulates the acutephase reaction, which enhances the innate immune system and protects against tissue damage [23].…”
Section: Discussionmentioning
confidence: 99%
“…It was found to be down-regulated in human asthmatic T cells 26 , and in mice elevated pro-inflammatory cytokines IL-6 and IL-1b were found as a result of miR-223 down-regulation upon induction with LPS 35 . In humans, IL-6 levels are known to be elevated in asthma and also correlate with lung function and IL-13 levels 36 . MiRNAs let-7a, miR-21, and miR-223 were shown to either directly or indirectly repress the translation of several crucial factors with well-defined roles in asthma pathogenesis, such as signal transducer and activator of transcription 3 (STAT3), interleukins (IL-6, IL-1b, IL-13), interferon gamma (IFN-c), transforming growth factor, beta receptor (TGF-b receptor), toll-like receptor 4 (TLR4), and vascular endothelial growth factor (VEGF) 3,4,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
mentioning
confidence: 99%